An evaluation of nurse preparation and practice in administering medicine to children - Hall, Carol (2002)
Administering medicine to children is a part of everyday nursing practice that is complex and multifaceted. However, medicine errors are prevalent in all areas of nursing. One means for strengthening a system of safe medicine administration might lie in developing student nurse preparation for registered practice.